Vibrio Population Dynamics in Mid-Atlantic Surface Waters during Saharan Dust Events - Westrich, Jason R.; Griffin, Dale W.; Westphal, Douglas L.; Lipp, Erin K. (Frontiers in Marine Science, 2018)
Vibrio is a cosmopolitan genus of marine bacteria, highly investigated in coastal and estuarine environments. Vibrio have also been isolated from pelagic waters, yet very little is known about the ecology of these oligotrophic species. In this study we examined the relative change in bacterial abundance and more specifically the dynamics of Vibrio in the tropical North Atlantic in response to the arrival of pulses of Saharan dust aerosols, a major source of biologically important nutrients for downwind marine surface waters. Aerosol and surface water samples were collected over one month coinciding with at least two distinct dust events. Total bacterial counts increased by 1.6-fold correlating with the arrival of Saharan dust (r=0.76; p=0.001). Virus-like particles also followed this trend and were correlated with bacterial counts (r=0.67; p=0.01). Vibrio specific qPCR targeting the 16S rRNA gene ranged from below detection limits to a high of 9,145 gene copies ml-1 with the arrival of dust. This increase equated to 6.5 x 10^2 – 1.5 x 10^3 individual genome equivalents ml-1 based on the known range of 16S rRNA copies among this genus. Vibrio exhibited bloom-bust cycles potentially attributed to selective viral lysis or bloom depletion of organic carbon. This work is one of the few studies to examine the open ocean ecology of Vibrio, a conditionally rare taxon, whose bloom-bust lifestyle likely is a contributing factor in the flow of nutrients and energy in pelagic ecosystems.